Palaeontological analysis of Middle Miocene siltstones at Wiślica (Carpathian Foredeep, Poland) - Płonka, Katarzyna (Instytut Geologii UAM, 2017)
Middle Miocene siltstones of the Skawina Formation that crop out at Wiślica, within the axial part of the Carpathian Foredeep in Poland, were analysed. The deposits studied contain numerous benthic and planktonic foraminifera, ostracods, echinoid spines, bryozoans, bivalves and otoliths. The fossils recognised document an early ‘Badenian’ (= Langhian in the Mediterranean area), or, more precisely, ‘Moravian’ age of the deposit. Palaeoecological analysis suggests normal-marine conditions with full salinity. The studied siltstones were deposited from middle–lower shoreface to lower–offshore, warm surface water and locally suboxic to dysoxic conditions in the sediment.
Keywords: microfossils; foreland basin; foraminifera; palaeoecology